Morphological characteristics and phylogenetic analyses revealed a new Calocybe (Lyophyllaceae, Basidiomycota) species from northeast China - Xu, Jize; Yu, Xiaodong; Zhang, Chunlan; Li, Yu (Phytotaxa, 2021)
A new species, Calocybe decurrens, is illustrated and described in detail based on morphological characteristics and phylogenetic analyses. Calocybe decurrens is mainly characterized by its decurrent gills and by its stipe that discolors upon maturation. Molecular phylogenetic analyses were based on the internal transcribed spacer (ITS1-5.8S-ITS2) and the large subunit of the nuclear ribosomal DNA (nrLSU) sequences. The results indicated that its affiliation is in genus Calocybe, where it occupies an isolated position. A full description, color images, illustrations and a phylogenetic tree to show the placement of the new species are provided.